Perancangan E-Commerce Pada Victory Collection Berbasis Web - Narti Eka Putria; Nurul Azwanti (Prosiding, 2023)
Along with developments in technology, companies are increasingly required to use advanced technology as a tool or media to survive and win the competition. The impact on the aspect of competition is the formation of an increasingly strong competition. The purpose of this research is to know how to design sales system at Victory Collection using web system; And to know how to optimize the sales system more effectively and efficiently at Victory Collection; As well as to find out how the solution to increase sales using a manual into a web-based system at Victory Collection. By using Waterfall Process Model method, all the system details that have been running and the system that will be proposed will be arranged and implemented to optimize the promotion and sales of existing products at Victory Collection. The Waterfall Process approach or method is a systematic and sequential systematic development model that starts at the level and progress of the system in all stages such as analysis, design, code, testing, and maintenance. This model covers activities such as engineering and modeling of information systems, needs analysis, design, coding, maintenance, and testing. The design of this information system is limited only to the food and beverage sales system. The results of this system is expected to minimize damage and loss of sales data and ordering goods at Victory Collection; And this system is expected to help facilitate the search and presentation of goods data at Victory Collection; And this system is expected to increase the sales ratio at Victory Collection.